PEMBELAJARAN MATEMATIKA DENGAN MENGGUNAKAN KECERDASAN MAJEMUK (MULTIPLE INTELLIGENCES) - Darlianita Mutiara Dalimunte (EDUTECH, 2023)
Education aims at person’s potency development process. Here, potency turns to competence. The competence is a mirror of person’s ability and skill for work. Teacher needs to know students’ talents, and smartness. The smartness is a reachable thing. Additionally, it is not only a thing person was born with, but it might be gained through supported situation like closed-relation communication.  There should be free time and opportunity for students to develop their own sense, creation and practice. Accordingly, mathematic students should stand alone to study through their potency. Being a primary subject, mathematic is not simple subject to study. Therefore, mathematic teacher should be creative and innovative. In conclusion, the teachers should have good technique and method to improve students’ multiple intelligences based on local and social characters for nation character